Investigation of optical properties of multilayer dielectric structures using prism-coupling technique. (30th September 2015) - Sokolov, V I; Glebov, V N; Malyutin, A M; Molchanova, S I; Khaydukov, E V; Panchenko, V Ya
Abstract A method based on resonant excitation of waveguide modes with a prism coupler is proposed for measuring the thickness and refractive index of thin-film layers in multilayer dielectric structures. The peculiarities of reflection of TE- and TM-polarised light beams from a structure comprising eleven alternating layers of zinc sulfide (ZnS) and magnesium barium fluoride (MgBaF4), whose thicknesses are much less than the wavelength of light, are investigated. Using the mathematical model developed, we have calculated the coefficients of reflection of collimated TE and TM light beams from a multilayer structure and determined the optical constants and thicknesses of the structure layers. The refractive indices of the layers, obtained for TE and TM polarisation of incident light, are in good agreement. The thicknesses of ZnS and MgBaF4 layers, found for different polarisations, coincide with an accuracy of ±1%. Thus, we have demonstrated for the first time that the prism-coupling technique allows one to determine the optical properties of thin-film structures when the number of layers in the structure exceeds ten layers.